Effect of Different Concentrations of Chitosan Biostimulant on Biochemical and Morphophysiological Traits of Stevia Plant (Stevia rebaudiana Bertoni) - M Mehregan; A Mehrafarin; MR Labbafi; HA Naghdi Badi (Institue of Medicinal Plants, ACECR, 2017)
Introduction: Chitosan is one of the polysaccharides containing nitrogen which is synthesized naturally by deacetylation reaction of chitin and is confirmed as one of the efficient biostimulants for improvement of secondary metabolites production in medicinal plants.  Objective: To evaluate the effect of different concentrations of chitosan biostimulant on vegetative biomass traits and secondary metabolites of Stevia plant. Methods: The experiment was conducted in a randomized complete block design with three replications in greenhouse conditions. The treatments were spraying of chitosan in four levels (0.05, 0.1 and 0.2 percent) and control treatment (spraying with distilled water). Results: In this study, the obtained results of variance analysis showed that spraying of chitosan had significant effect on leaf dry weight, shoot dry weight, leaf length (P <0.05), phenols and rebaudiosides A (P <0.01). In this experiment, the highest fresh and dry weight of stems, leaves and shoots were observed at 0.1% Chitosan in a way that by increasing the chitosan concentration from 0.1 to 0.2 % the decreasing trend occurred. The highest amount of phenol was recorded at 0.1% concentration. Also, chitosan at 0.2% concentration had the maximum impact on rebaudiosides A. Conclusion: Chitosan spraying improved vegetative biomass traits and biochemical parameters such as rebaudiosides A in stevia plant.